A church with the soul of a nation: making and remaking the United Church of Canada - Airhart, Phyllis D. (McGill-Queen's studies in the history of religion, 2014)
""As Canadian as the maple leaf" is how one observer summed up the United Church of Canada after its founding in 1925. But was this Canadian-made church flawed in its design, as critics have charged? A Church with the Soul of a Nation explores this question by weaving together the history of the United Church with a provocative analysis of religion and cultural change. The story begins in the aftermath of Confederation, when the prospects of building a Christian nation persuaded a group of Congregationalist, Methodist, and Presbyterian leaders to set aside denominational differences and focus instead on shared beliefs. Phyllis Airhart traces the new church's struggle to save its reputation during a bitter controversy with dissenting Presbyterians who refused to join what they considered a "creedless" church. Surviving the organizational and theological challenges of economic depression and war, the future of the church seemed bright. But the ties between personal faith and civic life that the founders took for granted were soon tattered by the secular cultural storm sweeping through western Christendom. The United Church's remaking came with the realization that creating a Christian social order in Canada was unlikely - perhaps even undesirable - in a pluralistic world. A Church with the Soul of a Nation sheds light on the United Church's past controversies and present dilemmas by showing how its founding vision both laid the groundwork for its accomplishments and complicated its adaptation to the new world taking shape."--Back cover